Exploring the Path of Contemporary Practice of Sinocization of Christianity: Taking Luzhou Church as an Example - Zhenyu LYU, (Journal of Research for Christianity in China (JRCC), 2024)
Adhering to the direction of the sinocization of Christianity is an inevitable requirement to follow the law of development of world religions and to promote the integration of Christianity into the Chinese nation, culture and society, which helps to enhance the identity of the majority of clergy and believers with the Chinese national community, and to forge a firm sense of the Chinese national community. This paper takes the Christian Church in Luzhou as an example, and discusses how the Church can promote the sinocization in the context of the new era in terms of political identity, cultural identity and social identity, so as to continuously adapt to the socialist society.
Keywords: sinocization of Christianity, social service, Luzhou, church